E-learning in elementary schools: educational system change during COVID-19 pandemic - S. Rafiqa; E. Boeriswati; H. Usman (Obrazovanie i Nauka)
Introduction. New digital technology in education and its constantly evolving paradigm have completely transformed the model of learning and the learning methods. E-learning has become an important tool for teaching and learning environments. Moreover, virtual learning has become a required alternative teaching method in educational system change during the COVID-19 pandemic, especially for learners in elementary schools.Aim. This research aimed to explore the necessities, lack, and want of learning English, which is done virtually at home.Methodology and research methods. This research employs descriptive methods using questionnaires and interviews as instruments to get responses from teachers and students about their learning needs. In the course of the needs analysis process, the importance and priority of teachers’ and students’ needs are discussed. The participants of this study were second-grade elementary school students, and the sample was 40 students and 2 English teachers for 10 months.Results. The research results demonstrate a gap between the needs of learners and current conditions; therefore, the whole language approach, the multimedia, and technology-based English teaching materials will become an inevitable need and even become a solution in the world of education.Scientific novelty. Further research is needed to study educational system change during the COVID-19 pandemic or after, especially in designing teaching materials in various disciplines and at different educational stages. Future studies could be generalised by these research findings to other populations in different learning contexts, and the findings presented in thisarticle should be further explored. In particular, technology-based and multimedia-based teaching materials must be explored more deeply. Furthermore, further research should focus on utilising a different model for needs analysis in language education to verify the need for effective English learning in changing the education system during the pandemic and after.Practical significance. It is thought that this study will contribute to the stakeholders in terms to provide empirical evidence of what necessities, lack, and want should be considered when a teacher will design and develop teaching materials during the COVID-19 period or afte.